1977
DOI: 10.1177/002242787701400207
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Barriers to Equal Justice before the Law

Abstract: Recently there has been growing concern with the degree to which the legal needs of the American public-and, more particularly, the poor in America-are being met. The inpetus for such concern has been the realization that if the protection of individual rights depends on income or social class, many individuals will not be guaranteed equal rights. Several studies have documented some of the structural barriers (primarily of an economic nature) to equal justice before the law. Others argue that while economic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Five of the ten statements concerned criminal law, such as: 'In a trial, the presumption of innocence means that an accused person must prove charges are false.' Similarly to Sarat's study, Albrecht and Green (1977) also found variation in legal knowledge about criminal law. Two of the five statements had a very high number of correct responses.…”
Section: Lay Knowledge Of Criminal Lawsupporting
confidence: 50%
See 2 more Smart Citations
“…Five of the ten statements concerned criminal law, such as: 'In a trial, the presumption of innocence means that an accused person must prove charges are false.' Similarly to Sarat's study, Albrecht and Green (1977) also found variation in legal knowledge about criminal law. Two of the five statements had a very high number of correct responses.…”
Section: Lay Knowledge Of Criminal Lawsupporting
confidence: 50%
“…Most studies analyse legal knowledge in light of a particular legal domain and a particular issue (family law and divorce rights, labour law and worker rights, health law, criminal law and education law). There are some broader studies that assess legal knowledge across domains (Williams and Hall 1972;Sarat 1975;Albrecht and Green 1977;Denvir, Balmer and Buck 2012;Denvir, Balmer and Pleasence 2013). Also, we see that some studies have focused on the legal knowledge of particular experts (doctors, teachers, school principals) and laypersons.…”
Section: The Existing Body Of Empirical Work On Legal Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…It is unreasonable to estimate perceptions of one part of the government while totally disregarding public views of other parts of the government (Ivkovic, 2008). Indeed, a strong relationship has long been observed between public attitudes toward police and other parts of the government (Albrecht & Green, 1977; Goldstein, 1977). On the basis of data from 28 countries, Ivkovic (2008) found that a significant determinant of public support for police was their thoughts about other state institutions, including the armed forces, Parliament, and legal system.…”
Section: Determinants Of Citizen Evaluation Of Policementioning
confidence: 99%